(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Developing strong reading skills is essential for students aiming to succeed in the Multilevel exam, which assesses a wide range of language competencies. Effective reading instruction requires strategic planning, targeted practice, and alignment with learners’ proficiency levels. This article explores key approaches to enhancing reading skills in the context of the Multilevel exam, focusing on text selection, comprehension strategies, and task-based learning. It also highlights the importance of differentiated instruction and formative assessment in addressing individual learning needs. By analyzing practical methods and pedagogical frameworks, this paper provides insights into designing reading-focused lessons that improve performance and foster independent, critical reading abilities.